The cybercrime and its efects in the theory of typicity: from a physical reality to a virtual reality (2017)
Cybercrimes are crimes with particular characteristics in regards to the action, the subject, the result and the imputation. Characteristics that show that the theory of crime must be complemented and revised again in some of its aspects, and in that way